Comparison of corneal biomechanics after microincision lenticule extraction and small incision lenticule extraction. Issue 5 (19th August 2016) - Wu, Zhiqing; Wang, Yan; Zhang, Jiamei; Chan, Tommy C Y; Ng, Alex L K; Cheng, George P M; Jhanji, Vishal
Abstract : Objectives: To evaluate and compare the change in corneal biomechanical properties after microincision lenticule extraction (MILE) and small incision lenticule extraction (SMILE). Methods: In this prospective study, 60 eyes received MILE surgery with 2 mm opening incision, while 64 eyes received SMILE procedure with 5 mm opening incision. Corneal hysteresis (CH), corneal resistance factor (CRF) and 37 other biomechanical waveform parameters were quantitatively assessed using ocular response analyser (ORA) preoperatively and up to 6 months postoperatively. All changes were calculated as the difference between preoperative and postoperative values (Δ). Results: Both CH and CRF values decreased significantly after MILE and SMILE (p<0.001). ΔCRF (o=0.028) and ΔCRF index (ΔCRF/preoperative CRF) (p=0.043) were statistically lower for all eyes at 1-week follow-up. ΔCH index (ΔCH/preoperative CH) was statistically lower at 1-week (p=0.043) and 1-month (p=0.015) follow-ups in MILE group when compared with SMILE group. In both MILE and SMILE group, ΔCH index and ΔCRF index were positively correlated with preoperative manifest refraction spherical equivalent, residual stromal thickness (RST) index (RST/preoperative central corneal thickness) and negatively correlated with lenticule thickness (p<0.05). Conclusions: Both MILE and SMILE procedures significantly altered the biomechanical characteristics of cornea. Smaller opening incision was associated with less reduction in ORA parameters during early postoperative period.